Working with Existing Databases - Murphy, Melissa; Alavi, Karim; Maykel, Justin (Clinics in Colon and Rectal Surgery, 2013)
Outcomes research has established itself as an integral part of surgical research as physicians and hospitals are increasingly required to demonstrate attainment of performance markers and surgical safety indicators. Large-volume and clinical and administrative databases are used to study regional practice pattern variations, health care disparities, and resource utilization. Understanding the unique strengths and limitations of these large databases is critical to performing quality surgical outcomes research. In the current work, we review the currently available large-volume databases including selection processes, modes of analyses, data application, and limitations.
Keywords: outcomes; databases; administrative; research